PENGARUH RETURN ON ASSET (ROA) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Siti Aisyah Siregar (Bussman Journal : Indonesian Journal of Business and Management, 2022)
Stock price is one of the things that can attract the attention of investors to invest in a company, and this is an important thing to be considered by the owners or leaders of the company. The purpose of this study is to find out what the effect of Return on Assets (ROA) and Net Profit Margin (NPM) on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange in 2017-2019. The research method used is a causal design method that aims to determine the influence between two or more variables. The data used is secondary data in the form of company financial statements obtained from www.idx.co.id. The results of this study stated that Return On Asset (ROA) partially had a significant effect on the stock price, while Net Profit Margin (NPM) was partially had no effect and was insignificant to the stock price. Simultaneously Return On Asset (ROA) and Net Profit Margin (NPM) have a significant influence on the stock price of food and beverage sector companies listed on the IDX in 2017-2019